PENGARUH MODEL PROJECT BASED LEARNING BERBANTUAN VIDEO INTERAKTIF TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA PADA PEMBELAJARAN IPAS DI KELAS IV SD NEGERI 5 TONJA DENPASAR - Yeloni, Ni Kadek Mila; Yasa, I Made Wiguna; Supadmini, Ni Kadek (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2026)
This study investigated the effect of the Project Based Learning ( PjBL ) model assisted by interactive video on the creative thinking skills of fourth-grade students at SD Negeri 5 Tonja . A quasi-experimental design with a non- equivalent control group was employed involving 64 students divided into experimental and control classes . Data were collected through multiple-choice tests and project assessment rubrics and analyzed using an independent sample t- test . The findings showed that the experimental class achieved a higher mean posttest score (80.13) than the control class (67.38), with a significant difference (p = 0.000). Therefore , PjBL assisted by interactive video effectively improved students ’ creative thinking skills .